KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DITINJAU DARI INTELLIGENCE QUOTIENT (IQ) PADA SISWA SMA NEGERI 6 SURAKARTA - Wahyumiarti, Wahyumiarti; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Journal of Mathematics and Mathematics Education, 2015)
Abstract: This study aims to analyze the ability of mathematical communication at students with a high, medium, and low IQ in grade XI MIA of State Senior High School 6 Surakarta in answering math questions. The subjects were 6 students that two students with high IQ, 2 students with medium IQ, and 2 students with low IQ. Techniques of data collection used documents and archives, a written test and an interview. Data analysis techniques used are data reduction, data presentation, and conclusion. The results of research showed that: (1) students with high IQ: in the mathematical written communication skills, students were able to create situations and proper solutions using the diagram, the students were also able to translate the ideas contained in the diagram with their own words in the form of detailed and structured information, and able to express ideas and opinions with good reason. In the mathematical verbal communication skills, the students were able to provide some information and the situation in the form of their own language, students were also able to express the right opinions to answer and respond questions in the form of a convincing argument and be able to make correct conclusions with emphatic pronunciation; (2) students with medium IQ: in the mathematical written communication skills, students were able to create situations and proper solutions to depict diagrams and adding several full details, students were also able to translate the ideas contained in the diagram with their own words which arranged in structured by providing some information, ideas and information, but students gave a brief opinion in giving reasons about diagram. In the mathematical verbal communication skills, the students were able to provide some information and situation into their own language forms in detail, complete, and structured, students were also able to give an opinion clearly and convincingly, in addition the student also gave some suggestions, and able to respond to questions in the form convincing argument and students were able to make the right conclusions but short explicitly; (3) students with medium IQ: in the mathematical written communication skills, students were able to create situations and appropriate solutions to describe the diagram and added some description, students were also able to translate the information contained in the diagram with their own sentences with ideas and information relating to the matter. In the mathematical verbal communication skills, students were able to give some brief information in the form of their own language, students were able to express opinions and suggestions but there is still less precise answer, the student was not able to properly respond to questions when giving an answer, but the students were able to make some conclusions short with a convincing argument.Keywords: Mathematical Communication, Math Questions, Intelligence Quotient